2020
DOI: 10.1126/sciadv.aaz7748
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni flows drive the alignment of fibrillar cell-laden hydrogels

Abstract: When a sessile droplet containing a solute in a volatile solvent evaporates, flow in the droplet can transport and assemble solute particles into complex patterns. Transport in evaporating sessile droplets has largely been examined in solvents that undergo complete evaporation. Here, we demonstrate that flow in evaporating aqueous sessile droplets containing type I collagen—a self-assembling polymer—can be harnessed to engineer hydrated networks of aligned collagen fibers. We find that Marangoni flows direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 44 publications
(51 reference statements)
2
44
0
Order By: Relevance
“…Whilst collagen fibrils have been located within fibripositors at the plasma membrane by electron microscopy, and cell culture studies have highlighted the importance of extrinsic mechanical forces (e.g. see 3639 ), cell-derived forces 40, 41 , combined mechanical anchoring and TGF β 1 cell activation 42 , and fluid flow 43 in generating an aligned network of collagen fibrils, mechanistic insights into how cells assemble collagen fibrils at the plasma membrane were lacking. Throughout the current study, collagen fibrils and Cy3-colI labelled fibrils were only seen in close proximity to the plasma membrane; fibrils unattached to cells and at distances from cells were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst collagen fibrils have been located within fibripositors at the plasma membrane by electron microscopy, and cell culture studies have highlighted the importance of extrinsic mechanical forces (e.g. see 3639 ), cell-derived forces 40, 41 , combined mechanical anchoring and TGF β 1 cell activation 42 , and fluid flow 43 in generating an aligned network of collagen fibrils, mechanistic insights into how cells assemble collagen fibrils at the plasma membrane were lacking. Throughout the current study, collagen fibrils and Cy3-colI labelled fibrils were only seen in close proximity to the plasma membrane; fibrils unattached to cells and at distances from cells were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…This self-assembly is a complex process that is controlled by the nanoparticle (physical and chemical properties of nanoparticle suspension, size, geometry, concentration), solvent, droplet geometry, substrate hydrophobicity, and evaporation kinetics. Previous work 17 has indeed demonstrated that the convective evaporation-induced assembly process can be strongly inuenced by convective uid particle transport, including the Marangoni ow, which arises from temperature and concentration gradients. [17][18][19][20] The self-assembled spherules organisation of bismuth nanosheets has not been reported before and demands further in-depth analysis.…”
Section: Resultsmentioning
confidence: 94%
“…Previous work 17 has indeed demonstrated that the convective evaporation-induced assembly process can be strongly inuenced by convective uid particle transport, including the Marangoni ow, which arises from temperature and concentration gradients. [17][18][19][20] The self-assembled spherules organisation of bismuth nanosheets has not been reported before and demands further in-depth analysis. Importantly, the spheruleslike superstructure with porous morphology could provide highly accessible surfaces, which would be benecial for high ion transport essential for energy storage devices.…”
Section: Resultsmentioning
confidence: 94%
“…the droplet volume, evaporation rate and collagen concentration. Such modelling will help to delineate the differences between the results of Nerger et al 19 , where only radial patterns are found, and the present work where both radial and concentric ring patterns reproducibly formed. Furthermore, it is not so clear why a concentration of 5 mg/ml yields a much more pounced topography than either 1 mg/ml or 10 mg/ ml.…”
Section: Discussionmentioning
confidence: 50%
“…In earlier phenomenological reports 17,18 , experiments revealed that remarkable well-ordered deposition patterns form by simply letting droplets consisting of a solution of collagen type I triple helices evaporate on a glass substrate. In a recent study this method has also been applied to radially orient skeletal muscle cells 19 . However, here we show a wider variety of collagen patterns to which tenocytes respond differently.…”
mentioning
confidence: 99%